2017
DOI: 10.3399/bjgpopen17x100977
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ attitudes and perceptions towards treatment of hypothyroidism in general practice: an in-depth qualitative interview study

Abstract: BackgroundSuboptimal thyroid hormone replacement is common in patients with hypothyroidism and the behavioural factors underlying this are poorly understood.AimTo explore the attitudes and perceptions of patients to thyroid hormone replacement therapy.Design & settingAn in-depth qualitative interview study with patients with hypothyroidism residing in Northumberland, and Tyne and Wear, UK.MethodTwenty-seven patients participated, of which 15 patients had thyroid stimulating hormone (TSH) levels within the refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
0
13
1
Order By: Relevance
“… 43 Poor levothyroxine adherence, medication interactions and comorbidities have been reported to have an effect on thyroid replacement therapy, 44 which were some of the barriers reported in this study. However, in our qualitative interview study with patients with hypothyroidism, although not generalisable outside of the patient population, good levothyroxine adherence was reported by nearly all patients, even those who had TSH levels outside of the reference range, 29 suggesting that the reasons for inadequate thyroid treatment may lie deeper than the typical assumptions by health professionals that poor adherence is the main reason for suboptimal treatment. 22 23 …”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“… 43 Poor levothyroxine adherence, medication interactions and comorbidities have been reported to have an effect on thyroid replacement therapy, 44 which were some of the barriers reported in this study. However, in our qualitative interview study with patients with hypothyroidism, although not generalisable outside of the patient population, good levothyroxine adherence was reported by nearly all patients, even those who had TSH levels outside of the reference range, 29 suggesting that the reasons for inadequate thyroid treatment may lie deeper than the typical assumptions by health professionals that poor adherence is the main reason for suboptimal treatment. 22 23 …”
Section: Discussioncontrasting
confidence: 54%
“…Deliberate TSH suppression (<0.1 mU/L) with high doses of levothyroxine, which was avoided by the majority of GPs in our study, is not recommended due to the potential risk of heart disease, stroke, osteoporosis and fractures. 41 In our previously published work with patients with hypothyroidism, patients felt that health professionals were more inclined to treat their TSH levels than their symptoms and that they were not given very much information at the time of diagnosis, 29 as reported by some health professionals in this study.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…34,35 Noteworthy, health care professionals acknowledge and underscore the difficulty of attributing symptoms to thyroid disease when with hormones-treated patient's clinical blood levels are within range. 36 Extra caution is therefore warranted when administering patients' additional thyroid hormones, just in case symptom are from their thyroid disease. 36 Interestingly, disease understanding was unrelated to HRQoL in our DTC survivors, although previous studies among other patient populations have also reported nonsignificant findings.…”
Section: Illness Perceptionsmentioning
confidence: 99%
“…36 Extra caution is therefore warranted when administering patients' additional thyroid hormones, just in case symptom are from their thyroid disease. 36 Interestingly, disease understanding was unrelated to HRQoL in our DTC survivors, although previous studies among other patient populations have also reported nonsignificant findings. 17,29 A former study among DTC patients revealed that a higher level of disease understanding was associated however with less negative emotional perceptions.…”
Section: Illness Perceptionsmentioning
confidence: 99%